A linear programming reformulation of the standard quadratic optimization problem - Klerk, Etienne de. (2013)
The problem of minimizing a quadratic form over the standard simplex is known as the standard quadratic optimization problem (SQO). It is NP-hard, and contains the maximum stable set problem in graphs as a special case. In this note,